USE OF STATIC PORTRAIT IN THE NOVEL "MAKHTUMKULI" BY THE WRITER K. MUHAMMADRIZO - Bayniyazov Azatbay Tursinbayevich (Scholar Express Journal, 2024)
In the article, the problems of artistic image and artistic portrait are discussed using the example of the novel "Makhtumkuli" by K. Muhammadrizo. As a result, the importance of static portrait, a type of artistic portrait used in the novel, and its role in creating historical figures and prototype images is determined
Keywords: novel; prototype; static portrait; historical figure